2020
DOI: 10.1017/s1366728920000310
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition of Spanish verbal morphology by child bilinguals: Overregularization by heritage speakers and second language learners

Abstract: The current study analyzes Spanish present tense morphology with a focus on overregularization. It examines written production from two groups of English/Spanish bilingual children in a dual immersion setting, Spanish heritage language (SHL) speakers (n = 21) and Spanish second language (SL2) learners (n = 41), comparing them to age-matched (nine to ten years old) Spanish majority language children (n = 15). Spanish majority children show full mastery of present tense regular, stem-changing and irregular morph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 48 publications
1
4
0
Order By: Relevance
“…They found that the higher the parental mixed language use rate, the lower the children's vocabulary comprehension ability, which indicates that a mixed-language environment has an inhibitory effect on children's new vocabulary acquisition, and this inhibitory effect begins to appear from 1.5 years of age [17]. This result is consistent with other studies that show that bilingual children in a mixed-language environment lag behind monolingual children in language and vocabulary learning [29,[32][33][34]. Fernández-Dobao and Herschensohn used two writing tasks to compare the grammatical ability of Spanish bilingual children and monolingual children.…”
Section: Vocabulary Learning In Children In a Mixed-language Environmentsupporting
confidence: 81%
See 1 more Smart Citation
“…They found that the higher the parental mixed language use rate, the lower the children's vocabulary comprehension ability, which indicates that a mixed-language environment has an inhibitory effect on children's new vocabulary acquisition, and this inhibitory effect begins to appear from 1.5 years of age [17]. This result is consistent with other studies that show that bilingual children in a mixed-language environment lag behind monolingual children in language and vocabulary learning [29,[32][33][34]. Fernández-Dobao and Herschensohn used two writing tasks to compare the grammatical ability of Spanish bilingual children and monolingual children.…”
Section: Vocabulary Learning In Children In a Mixed-language Environmentsupporting
confidence: 81%
“…They found that bilingual children showed overregularization phenomena when using inflected verbs, indicating that bilingual children were not as good as monolingual children in learning and using Spanish verb morphology. They argued that this was because bilingual children had to master two different verb morphology systems at the same time, thus facing more linguistic complexity in language learning [32]. Morini et al also supported this view.…”
Section: Vocabulary Learning In Children In a Mixed-language Environmentmentioning
confidence: 98%
“…Dual language immersion programs teach academic content such as math, science, reading and writing in English and a partner language, most frequently Spanish, given its prevalence in many U.S. communities. There are several studies that examine language acquisition in children attending Spanish-English immersion schools (Gathercole, 2002;Herschensohn et al, 2005;Potowski, 2005Potowski, , 2007aMontrul and Potowski, 2007;Fernández-Dobao andHerschensohn, 2020, 2021;Goldin, 2020Goldin, , 2021Sánchez et al, 2023), but few of them focus on the development of Spanish in bilingual children between 7-18 years old. Montrul (2018, p. 534) argues that bilinguals in this age span are the "missing link" of heritage language research, as they are essential to charting the path of acquisition between preschool, an age range for which there is more abundant research evidence from bilingual children, and adulthood, where HS frequently show grammatical innovations not found in monolingual grammars.…”
Section: Introductionmentioning
confidence: 99%
“…First, the number of different verb types used by the children can be taken as an indicator of the richness and diversity of the bilingual lexicon. Second, we focus on verb morphology, which is often shown to be demanding for heritage speakers (HSs), for instance in Russian (Mikhaylova, 2018) or in Spanish as HL (Fernández-Dobao & Herschensohn, 2021), particularly in experimental studies. We analyse whether this also applies to bilingual children's written production of tense, aspect and agreement morphology in European Portuguese (EP) as HL.…”
Section: Introductionmentioning
confidence: 99%